Rehabilitation outcomes of a lifestyle intervention program for chronic disease medical insurer referred and funded patients versus self-initiated and self-funded patients. - Hope, Fallon (MRC/UCT RU for Exercise and Sport Medicine, 2014)
Includes abstract.